VARIETAL PERFORMANCE AND CORRELATION OF OKRA POD YIELD AND YIELD COMPONENTS (Bangladesh Journal of Plant Breeding and Genetics, 2017)
Field irrigation experiments were conducted to assess the varietal performance and correlation of pod yield and yield attributes under irrigation at the Teaching and Research Farm, University of Maiduguri, Nigeria, during 2015 and 2016 dry seasons. The results revealed that the most outstanding for fresh pod yield per plant were okra cultivar Kwadag Yar gagure Salkade and, Kwadam in descending order with yield ranging from 580.38-622.67g, while the composite cultivar had the lowest value of pod yield of 428.62g over the two years. The highest mean values for number of pods per plant and number of primary branches per plant were observed for Salkade and Yar gagure, respectively. Highest fresh pod length and fresh pod diameter were also exhibited for Salkade and Kwadag, respectively. Genotypic coefficient of variation was higher than the phenotypic variation for all the yield contributing characters. Days to 50% flowering were positive and highly significance difference associated with plant height, number of pods per plant and fresh weight per pod. Path coefficient analysis showed that number of pods per plant exhibited positive and direct effects on pod yield across years. Indirect effect of other yield components through this character also contributed mainly towards pod yield. Therefore, plant height, days to 50% flowering, number of pods per plant, pod length, pod diameter, number of primary branches per plant and fresh weight per pod could be considered for selection and improvement for high pod yielding varieties in okra.